Switchable photovoltaic windows enabled by reversible photothermal complex dissociation from methylammonium lead iodide - Lance M. Wheeler (Nature Portfolio, 2017)
Conventional smart windows with tunable transparency are based on electrochromic systems that consumes energy. Here Wheeler et al. demonstrate a halide perovskite based photo-switchable window that dynamically responds to sunlight and change colors via reversible phase transitions.